The LRRK2 R1628P Variant Plays a Protective Role in Han Chinese Population with Alzheimer's Disease - Li, Hong‐Lei (CNS Neurosci Ther, 2013)
AIMS: Alzheimer's disease (AD) and Parkinson's disease (PD) are the most prevalent neurodegenerative disorders that may share some overlapping etiologies. Mutations within leucine‐rich repeat kinase 2 (LRRK2) have been reported to be responsible for PD, and the location of LRRK2 is within a linkage peak for sporadic AD (SAD). The aim of this study was to investigate two Asian‐specific LRRK2 variants, R1628P and G2385R, with the association of Han Chinese SAD. METHODS: Genotyping of R1628P and G2385R was performed by PCR‐restriction fragment length polymorphism (RFLP) analysis in 390 patients with SAD and 545 unrelated age‐ and sex‐matched healthy controls. RESULTS: The frequency of the C allele within R1628P was more than three times higher in control group (1.7%) than in patients with SAD (0.5%) (OR 0.264; 95% CI, 0.088–0.792, P = 0.018). After stratification by the presence of one or two apolipoprotein E ε4 alleles, the protective effect becomes stronger (ε44: OR 0.028; 95% CI, 0.003–0.303, P = 0.003; ε4: OR 0.104; 95% CI, 0.013–0.818, P = 0.031). However, no difference was found in G2385R variant. CONCLUSION: Our study suggested that R1628P variant within LRRK2 plays a protective role in Han Chinese population with SAD and such effect has an interaction with the APOE genotype.